MECHANISM OF DEVELOPMENT OF SINUS ARRHYTHMIA - Rashidova Maftuna Shermatov Bektosh Ermatov Farrux Jòraboyev Ozodbek (Journal of Science in Medicine and Life, 2024)
The sinus node is a group of cells in the wall of the heart that produce electrical impulses. It is in the sinus node that the normal heartbeat impulse begins to form. It flows along the fibers of the heart wall, which is called the conduction system. This system is divided into many fibers, and the smallest of them ends in each fiber of the heart wall. This mechanism ensures rhythmic and harmonious functioning of the heart (contractions occur at equal intervals, maintaining the optimal frequency of 60-90 per minute).